ANALYSIS OF THE FACTORS AFFECTING THE CONSUMER PURCHASING DECISIONS ON COFFEE AT RESTO BANARAN 9, GEMAWANG VILLAGE, SEMARANG - asnita lase; Agus Setiadi; Kustopo Budiraharjo (AGROLAND: The Agricultural Sciences Journal, 2019)
This study aims to determine the general description of Resto Banaran 9, to analyze general description of coffee consumers in Resto Banaran 9 which includes respondent characteristics, consumption behavior, and respondent’s answer distribution,in additionto analyze the influence of cultural factors, social factors, personal factors, psychological factors, and physical evidence on coffee purchasing decisions at Resto Banaran 9. This research was conducted on 10 September until 11 October 2018 at Resto Banaran 9, Gemawang Village, Jambu Sub-district, Semarang District. The location of the research was determined purposively. This research method was a survey and data collection techniques through interviews using a questionnaire tool distributed to 100 respondents. The sampling method used was the accidental sampling method. Data analysis used was descriptive-quantitative analysis method. The quantitative analysis used was multiple linear regression analysis. The results showed that simultaneously, cultural factors, social factors, personal factors, psychological factors, and physical evidence had a significant effect on consumers’ coffee purchasing decisions at Resto Banaran 9. Moreover, partially, cultural factors, social factors, personal factors, psychological factors, and physical evidence had a significant effect on consumers’ coffee purchasing decisions at Resto Banaran 9.